2020
DOI: 10.1332/175982720x15971673526089
|View full text |Cite
|
Sign up to set email alerts
|

The impact of precarious employment on the health and wellbeing of UK immigrants: a systematic review

Abstract: This article synthesises evidence on the experiences of immigrants in the United Kingdom who are engaged in precarious employment and explores the effects of precarious employment on their health and wellbeing. This study reveals that migrants in precarious employment often experience negative health outcomes including injury, anxiety and depression. Stress response theories and risk factors associated with occupational injury help explain how employment specific factors influence health. The study shows that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Therefore, further studies need to extend and address the theoretical pathways between policies, labor market conditions, and the association between precarious employment and health. Moreover, theoretical debates should explore how to include factors such as life course, 136 migration, 137 or gender, 138 which play an important role when explaining the extent and form of differences in health by precarious employment. This requires an interdisciplinary work between scholars from occupational health research, medical sociology, public health, politics, psychology, and epidemiology.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further studies need to extend and address the theoretical pathways between policies, labor market conditions, and the association between precarious employment and health. Moreover, theoretical debates should explore how to include factors such as life course, 136 migration, 137 or gender, 138 which play an important role when explaining the extent and form of differences in health by precarious employment. This requires an interdisciplinary work between scholars from occupational health research, medical sociology, public health, politics, psychology, and epidemiology.…”
Section: Discussionmentioning
confidence: 99%
“…Although new perpetual foreign worker admittance is now quite a few, transitory foreign worker employment looks to be getting more common; certain nations are implementing governmental steps to support it. The temporary employment of foreign workers adds versatility to the labor market and helps to alleviate sectoral labor scarcity in host countries (Muoka & Lhussier, 2020;Urbański, 2021). The latter is especially true in the latest technological segments, where numerous countries are experiencing a shortage of qualified and highly competent laborers.…”
Section: Reasons For Foreign Employment Migrantsmentioning
confidence: 99%
“…A Maltese study found that half of the immigrant respondents indicated that their health or safety is at risk because of their work (Debono and Vassallo, 2019). In addition, a review study in the UK found positive associations between adverse working conditions and deteriorated physical and mental health status including injury, anxiety and depression (Muoka and Lhussier, 2020).…”
Section: A Adverse Working Conditions and Physical And Mental Healthmentioning
confidence: 99%